287 Effects of copper hydroxychloride on growth performance and abundance of genes involved in lipid metabolism of growing pigs - Espinosa, Charmaine (J Anim Sci, 2020)
An experiment was conducted to test the hypothesis that Cu hydroxychloride (IntelliBond C(II), Micronutrients, LLC, Indianapolis, IN) improves growth performance by upregulating the mRNA transcription of genes involved in lipid metabolism of pigs. Thirty-two pigs (15.05 ± 0.98 kg) were allotted to 2 dietary treatments with 2 pigs per pen for a total of 8 replicate pens per treatment. Pigs were fed a control diet based on corn, soybean meal, and distillers dried grains with solubles that included Cu to meet the requirement. A second diet was formulated by adding 150 mg Cu/kg from Cu hydroxychloride to the control diet. On the last day of the experiment, one pig per pen was sacrificed and samples from liver, skeletal muscle, and subcutaneous adipose tissue were collected to analyze relative mRNA abundance of genes involved in lipid metabolism. Data were analyzed using SAS with pen as the experimental unit. Diet was the fixed effect and replicate was the random effect. Results indicated that overall average daily gain and gain:feed were greater (P < 0.05) for pigs fed the diet containing Cu hydroxychloride compared with pigs fed the control diet (Table 1). Pigs fed the diet supplemented with Cu hydroxychloride had increased (P < 0.05) abundance of cluster of differentiation 36 in liver and increased (P < 0.05) abundance of fatty acid binding protein 4 and lipoprotein lipase in subcutaneous adipose tissue. Inclusion of Cu hydroxychloride also tended to increase (P < 0.10) abundance of fatty acid binding protein 1, peroxisome proliferator-activated receptor alpha, and carnitine palmitoyl transferase 1 B in liver, skeletal muscle, and subcutaneous adipose tissue, respectively. In conclusion, supplementation of Cu hydroxychloride to the control diet improved growth performance and may affect signaling pathways associated with lipid metabolism by upregulating abundance of some genes involved in post-absorptive metabolism of lipids. [Image: see text]